2002
DOI: 10.1002/prot.10137
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilt 3D structure of the chloroplast f1 ATPase–tentoxin complex

Abstract: The F1 part of the chloroplast H+ adenosine triphosphate (ATP)-synthase (CF1) strongly interacts with tentoxin, a natural fungous cyclic tetrapeptide known to inhibit the chloroplast enzyme and not the mammalian mitochondrial enzyme. Whereas the synthesis or the hydrolysis of ATP requires the stepwise rotation of the protein rotor gamma within the (alphabeta)3 crown, only one molecule of tentoxin is needed to fully inhibit the complex. With the help of an original homology modeling technique, based on robust d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(87 reference statements)
0
9
0
1
Order By: Relevance
“…These enzymes couple a downhill proton flow with ATP synthesis through adenosine diphosphate (ADP) photophosphorylation. , The ATP synthases can be biochemically fragmented into two different subcomplexes, known as F 0 and F 1 (CF 0 and CF 1 in chloroplasts). The CF 0 complex is membranous and acts as the proton channel, whereas the CF 1 moiety is a soluble α 3 β 3 γδε complex which is capable of ATP hydrolysis . Crystal structures determined for several F 1 ATPases and corresponding subcomplexes revealed that these multichain enzymes are structured (ordered) and highly organized entities. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes couple a downhill proton flow with ATP synthesis through adenosine diphosphate (ADP) photophosphorylation. , The ATP synthases can be biochemically fragmented into two different subcomplexes, known as F 0 and F 1 (CF 0 and CF 1 in chloroplasts). The CF 0 complex is membranous and acts as the proton channel, whereas the CF 1 moiety is a soluble α 3 β 3 γδε complex which is capable of ATP hydrolysis . Crystal structures determined for several F 1 ATPases and corresponding subcomplexes revealed that these multichain enzymes are structured (ordered) and highly organized entities. , …”
Section: Resultsmentioning
confidence: 99%
“…The CF 0 complex is membranous and acts as the proton channel, whereas the CF 1 moiety is a soluble α 3 β 3 γδε complex which is capable of ATP hydrolysis . Crystal structures determined for several F 1 ATPases and corresponding subcomplexes revealed that these multichain enzymes are structured (ordered) and highly organized entities. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we show, through the example of tentoxin (TTX), that such intermediates may occur more regularly than reported in the metabolism of natural N ‐methylated cyclopeptides. TTX [cyclo‐( l ‐ N‐ MeAla 1 ‐ l ‐Leu 2 ‐ N‐ Me(Δ Z )Phe 3 ‐Gly 4 ] (Scheme 2) is a natural hydrophobic cyclotetrapeptide which acts in certain plant species as a noncompetitive inhibitor of chloroplast ATP‐synthase [29–31], provoking chlorosis. We have previously shown that TTX is efficiently metabolized through N ‐demethylation by mammal cytochrome P450 [32].…”
Section: Introductionmentioning
confidence: 99%
“…Using a photoactivatable TTX analogue, we found that TTX specifically binds the R subunit of CF 1 -. We then docked TTX in its putative site located at the three possible R/β interfaces of a rebuilt 3D structure of CF 1 R 3 β 3 γ subcomplex, made asymmetrical after insertion of γ subunit (28). Kinetic experiments performed on CF 1 -using well-characterized TTX analogues as competitors revealed how the inhibitory site influences the reactivatory site, whereas chase experiments using 14 C-labeled TTX showed that the reactivatory site has no influence on the binding properties of the inhibitory site.…”
mentioning
confidence: 99%